A Verification And Validation Of Business Process Modeling Using Petri Nets (Case Study of Telkom University FRI Laboratory Business Architecture Domain) - Alvan Kamal; Muharman Lubis; Fitriyana Dewi; Matias Garcia Constantino (Electronic Integrated Computer Algorithm Journal, 2023)
Enterprise Architecture is an approach that is present to form a sustainable organization. However, the average company that has implemented Enterprise Architecture does not see and does not know whether the existing business processes in the company are currently running well, and have been effective and efficient in achieving company goals or not. These conditions make validation and verification of business processes important. In this research, business process testing using the Scrum method with Petri Nets supported by WoPed tools is considered to verify and validate the business architecture design. Testing using the Scrum method is carried out through six stages, namely product backlog, sprint planning, sprint backlog, sprint review, and sprint retrospective. The test results show that several requirements are not met. This condition will have an impact on the efficiency and effectiveness of business processes. Furthermore, gap analysis is carried out with dependencies analysis, there are business processes that have not been verified and validated due to errors in the process that cause time constraints to work on more than one task simultaneously optimally, there is a process stage that is too long so that it hampers the efficiency and effectiveness of business processes.